Development of a Surgical Video Atlas for Resident Education: 3-Year Experience. Issue 3 (July 2020) - Brown, C. Scott; Cunningham, Calhoun D.; Lee, Walter T.; Puscas, Liana
Objective: To create a high-quality annotated online surgical video atlas of key indicator otolaryngology cases and assess its use and overall journal trends over time. Methods: Videos are recorded from multiple viewpoints within the operating room and compiled into a single stream. Postediting includes chaptering videos and overlaying relevant text annotations. Videos are published online and viewership trends analyzed. Results: Over 3 years, 29 otolaryngology videos were published out of 161 journal publications (18%). Eight of the 14 key indicator procedures are included (57%). From the beginning of 2017 to the end of 2019, viewership of otolaryngology pages increased from 548 to 11, 139 views per month, totaling >150, 000 views. These now represent 10% of the total journal monthly views and 10% of the overall views. Users originate from the United States and from >10 other countries. Discussion: Residents and faculty face challenges of providing the highest standard of clinical care, teaching, and learning in and out of the operating room. Inherent difficulties of surgical training, high-fidelity surgical simulation, and imposed work hour restrictions necessitate additional, more efficient and effective means of teaching and learning. Surgical videos demonstrating key anatomy, procedural steps, and surgical dexterity with hand positioning are increasing in their popularity among learners. Implications for Practice: Surgical video atlases provide a unique adjunct for resident education. They are enduring and easily accessible. In a climate of work hour restrictions or elective case reduction, they may supplement how residents learn to operate outside the operating theater.